Pengaruh Minat Belajar Siswa pada Mata Pelajaran Produk Kreatif dan Kewirausahaan terhadap Prestasi Siswa Kelas XI SMK Kompetensi Keahlian Teknik Elektronika Industri - Ice Faulia; Dias Andris Susanto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
The study was conducted to determine the effect of students' interest in learning in the subjects of Creative Products and Entrepreneurship on the achievements of students of class XI SMK Competence in Industrial Electronics Engineering. This research is a quantitative study, quantitative research emphasizes the process so that in seeing the relationship between variables in the object under study are more interactive that is the mutual influence. Subjects studied were the Effect of Entrepreneurial Characteristics on Subjects of Creative Products and Entrepreneurship on the Achievement of Grade XI Students in Industrial Electronics Engineering at SMKN 4 Semarang. The source of data in this study is the XI grade students of Industrial Electronics Engineering at SMKN 4 Semarang in the academic year 2018/2019. With a sample of 70 students to test the increase in learning achievement. This class action research was conducted with the Classroom Action Research method which consisted of 2 cycles. Actions in each cycle are interrelated, The steps of each cycle consist of: Making Planning (planning), carrying out actions according to planned (acting), observing the actions to be performed (Observing), reflecting descriptive comparative (reflecting). Data obtained from test results and questionnaire. The analysis technique used is the Normality Test, R square Test, ANOVA Test to determine the magnitude of the influence of several indicators in the study.